Occupational exposure to solvents and male infertility. Issue 10 (1st October 2001) - Cherry, N; Labrèche, F; Collins, J; Tulandi, T
Abstract : OBJECTIVES: To determine whether, in a case-referent study of infertility patients, cases with low motile sperm count were more likely than referents to have had exposure to organic solvents. METHODS: Occupations of men attending fertility clinics in Canada were assigned codes reflecting probable exposure to organic solvents, at four grades of intensity, using a job exposure matrix previously developed. A case referent design was used, with cases being defined as men with <12×10 6 /ml motile sperm. Information from 656 men in manual work attending a single clinic in Montreal in 1972–91 was used for the main study. A separate analysis was conducted with information for 574 men in manual work attending 10 further clinics across Canada in 1984–7. RESULTS: In the Montreal series a significant association was found between intensity of exposure to solvents and clinical findings of <12×10 6 /ml motile sperm. Odds ratios (ORs), after allowing for confounding, were 2.07 (95% confidence interval (95% CI) 1.24 to 3.44) for moderate exposure to solvents and 3.83 (95% CI 1.37 to 10.65) for high exposure. In the second series of 568 men, the effect was confirmed at high exposure to solvents (OR 2.90, 95% CI 1.01 to 8.34) but not at moderate exposure (OR 1.01, 95% CI 0.53 to 1.92). CONCLUSIONS: Exposure to organic solvents is common both at work and in recreational pursuits. The results of this study suggest that efforts should be made to identify the compounds hazardous to male fertility, and if the risk is confirmed, to regulate their use.